Les États-Unis, la propagande et la guerre : de Cuba (1898) à l’Irak (2003) - Fredj Maatoug (Revue LISA)
In 1897 Theodore Roosevelt wrote to a friend “I should welcome almost any war, for I think this country needs one”. He was thinking in his deep consciousness that “the Empire” needed war. In 1898 “the splendid little war” against Spain in Cuba was the answer to this expectation. Many decades later, following the dislocation of the USSR and the end of the Cold War, the USA emerged as the only superpower. It was in this context that the September 11 attacks took place. In 2003, Washington declared war on Iraq despite the international opposition. The USA waged a tremendous PR campaign to convince public opinion of the potential threat of Iraqi weapons of mass destruction and of the involvement of the Saddam Hussein regime in the attacks against the World Trade Center. None of these reasons proved to be true, but the war showed the strength of different political and industrial lobbies.